The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1023/a:1025051214001
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The role of various matrix metalloproteinases (MMP)--such as gelatinases, stromelysins, matrilysin, collagenase-3, and membrane-bound MMP (MB-MMP)--in tumor invasion and metastasis is discussed. Data suggesting significance for malignant growth of the expression level of these enzymes and also of their activators and inhibitors are presented. It is concluded that at different stages of tumor progression the activity of different MMPs is displayed, which is regulated by various growth factors and oncogenes. Dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 52 publications
1
19
0
Order By: Relevance
“…MMPs that are highly expressed in various malignant tumors have been recognized as playing an important role in cell motility and invasion via the degradation of ECM components of blood or lymph vessels (Khasigov et al ., 2003; Hanahan and Weinberg, 2011). Gelatinase types of MMPs such as MMP-2 and -9 promote tumor cell invasion in various cancer cell lines because of their ability to degrade various types of collagens (Vu and Werb, 2000; Egeblad and Werb, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MMPs that are highly expressed in various malignant tumors have been recognized as playing an important role in cell motility and invasion via the degradation of ECM components of blood or lymph vessels (Khasigov et al ., 2003; Hanahan and Weinberg, 2011). Gelatinase types of MMPs such as MMP-2 and -9 promote tumor cell invasion in various cancer cell lines because of their ability to degrade various types of collagens (Vu and Werb, 2000; Egeblad and Werb, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Metastasis is a highly coordinated multistep process, of which degradation of the extracellular matrix (ECM) is an important component (Khasigov et al ., 2003; Hanahan and Weinberg, 2011). Through degradation of the ECM, cancer cells escape the primary tumor, penetrate the basement membrane of capillary and lymphatic vessels, intravasate, and migrate to new locations in the body (Yilmaz et al ., 2007; Valastyan and Weinberg, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the results of the invasion assay showed that the invasion of CT26 and HT29 cells was attenuated by G.A treatment ( Figure 7C ). The gelatinase activity of MMP-2 and MMP-9 is closely related to the invasiveness of cancer cells (Khasigov et al, 2003). We observed that G.A reduced the expression levels of MMP-2 and MMP-9 using IF analysis ( Figure 7D ).…”
Section: Resultsmentioning
confidence: 99%
“…A typical feature of EMT is the loss of cell-cell contact by the regulation of expression of cell-cell adhesion molecules such as E-cadherin, N-cadherin, and vimentin (Thiery and Sleeman, 2006). Additionally, epithelial cancer cells become spindle shaped with increased metastatic abilities including migration and invasion by enhancing matrix metalloproteinase (MMP)-2 and MMP-9 production, which are involved in matrix remodeling-related proteolysis (Khasigov et al, 2003). …”
Section: Introductionmentioning
confidence: 99%